The Toughest Material in the Plant Kingdom: An Update on Sporopollenin - Grienenberger, Etienne; Quilichini, Teagen D. (Frontiers in Plant Science, 2021)
The extreme chemical and physical recalcitrance of sporopollenin deems this biopolymer among the most resilient organic materials on Earth. As the primary material fortifying spore and pollen cell walls, sporopollenin is touted as a critical innovation in the progression of plant life to a terrestrial setting. Although crucial for its protective role in plant reproduction, the inert nature of sporopollenin has challenged efforts to determine its composition for decades. Revised structural, chemical and genetic experimentation efforts have produced dramatic advances in elucidating the molecular structure of this biopolymer and the mechanisms of its synthesis. Bypassing many of the challenges with material fragmentation and solubilization, insights from functional characterizations of sporopollenin biogenesis in planta, and in vitro, through a gene-targeted approach, suggest a backbone of polyhydroxylated polyketide-based sub-units and remarkable conservation of biochemical pathways for sporopollenin biosynthesis across the plant kingdom. Recent optimization of solid-state NMR and targeted degradation methods for sporopollenin analysis confirm polyhydroxylated -pyrone subunits, as well as hydroxylated aliphatic units, and unique cross-linkage heterogeneity. We examine the cross-disciplinary efforts to solve the sporopollenin composition puzzle, and illustrate a working model of sporopollenin’s molecular structure and biosynthesis. Emerging controversies and remaining knowledge gaps are discussed, including the degree of aromaticity, cross-linkage profiles, and extent of chemical conservation of sporopollenin among land plants. The recent developments in sporopollenin research present diverse opportunities for harnessing the extraordinary properties of this abundant and stable biomaterial for sustainable microcapsule applications and synthetic material designs.